Antibacterial Activity of Some Herbs Water Extract against Escherichia coli - Prakoso, Bondan; Widodo, Eko; Sudjarwo, Edhy (The Journal of Experimental Life Science, 2015)
The research aims to select the highest diameter inhibition zone of several types of herb water extract against Escherichia coli and find the best herb water extract towards minimum inhibition concentration. It was divided into two parts, in the first stage was to evaluate antibacterial activity of herbs water extract and the second stage was to evaluate concentration of extract to effectively inhibit growth of E. coli. In the first experiment there were 6 treatments; P0 (aquadest 100%), P1 (antibiotic tetrachlor), P2 (Zingiber officinale extract), P3 (Z. officinale var. Rubrum extract), P4 (Kaempferia galanga extract) and P5 (Z. zerumbet L. extract) tested to find the best herbs on the basis of diameter inhibition zone. In the second experiment 6 treatments were used namely from 0%, 50%, 60%, 70%, 80%, 90% and 100% of Z. officinale var. Rubrum extract tested for Minimum Inhibition Concentration (MIC) against E. coli. The results showed that among the herbs, Z. officinale var. Rubrum extract had the strongest antibacterial activity based on diameter of inhibition zone against E. coli. While as low as 50% of Z. officinale var. Rubrum extract showed an MIC although the highest activity indicated when 100% of Z. officinale var. Rubrum extract used.Keywords: Z. officinale var. Rubrum, diameter of inhibition zone, MIC and E. coli.